Intracellular ROS levels determine the apoptotic potential of keratinocyte by Quantum Dot via blockade of AKT Phosphorylation. Issue 11 (12th July 2017) - Lee, Eun Young; Bae, Hyun Cheol; Lee, Hana; Jang, Yeonsue; Park, Yoon‐Hee; Kim, Jin Hee; Ryu, Woo‐In; Choi, Byeong Hyeok; Kim, Ji Hyun; Jeong, Sang Hoon; Son, Sang Wook
Abstract: Quantum dots (QDs) have shown great potential for biomedical use in a broad range including diagnostic agents. However, the regulatory mechanism of dermal toxicity is poorly understood. In this study, we investigated how QDs‐induced apoptosis is regulated in human keratinocytes. We also examined the effect of carboxylic acid‐coated QDs (QD 565 and QD 655) on reactive oxygen species (ROS) production and apoptosis‐related cellular signalling. The viability of keratinocyte was inhibited by two types of QDs in a concentration‐dependent manner. QDs induce ROS production and blockade of AKT phosphorylation. Moreover, the cleavage of AKT‐dependent pro‐apoptotic proteins such as poly (ADP‐ribose) polymerase, caspases‐3 and caspases‐9 was significantly increased. We also found that a decrease in cellular ROS level by ROS scavenger, N‐acetylcysteine (NAC), resulting in the abolishment of QDs‐induced AKT de‐phosphorylation and cellular apoptosis. Interestingly, QD 655 had a more cytotoxic effect including oxidative stress and AKT‐dependent apoptosis than QD 565. In addition, QD 655 had the cytotoxic potential in the human skin equivalent model (HSEM). These data show that QD‐induced intracellular ROS levels may be an important parameter in QD‐induced apoptosis. These findings from this study indicate that intracellular ROS levels might determine the apoptotic potential of keratinocyte by QD via blockade of AKT phosphorylation.